Frequency of pulmonary hypertension in chronic kidney disease patients (stages 3, 4, 5) at a tertiary care hospital - Zahidul Islam, M.; Akter, Tania; Mijanur Rahman, A. K. M. (International Journal of Research in Medical Sciences, 2024)
Background: Chronic kidney disease (CKD) is a challenging issue for health care providers and major burden for health care. Cardiovascular disease is a well-recognized and important source of mortality in a patient with chronic kidney disease. The aim of this study was to observe the frequency of pulmonary hypertension in chronic kidney disease patients at tertiary care hospital. Methods: This cross sectional observational study was conducted in the Department of Medicine, Combined Military Hospital, Dhaka Cantonment, Bangladesh over a period of six months from 17th November 2019 to 16th May 2020. Results: It was observed that majority, e.g., 28.0% patients belonged to age 41-50 years, mean age was found 41.4±9.7 years in Group-A and 42.1±8.5 years in Group-B. On evaluation of eGER, maximum patients (e.g., 61%) had <15 ml/min/1.73 m2, followed by 24.0% of patients had 15-29 ml/min/1.73 m2 and 15.0% case detected 30-59 ml/min/1.73 m2. Standard 2D, M mode echocardiographic was conducted in all patients. In this study, mPAP<25.0 mmHg was detected in 31 (62.0%) and 45 (90.0%) in group A and group B respectively. Overall prevalence of pulmonary hypertension was 24.0%. On comparison between groups, it is evident that frequency of pulmonary hypertension was predominant in patients with chronic kidney disease on maintenance haemodialysis than patients with chronic kidney disease without maintenance haemodialysis (38.0% vs. 10.0% respectively). Conclusions: Pulmonary hypertension (PH) is common in patients with chronic kidney disease and is an independent predictor of mortality.